先天性第V因子欠乏症の周術期第V因子活性管理を行った舌癌患者の1例 - 深町, 恵; 丹沢, 秀樹; 鵜澤, 一弘; 宮本, 勲; 喜田, 晶洋; 齋藤, 智昭 (日本口腔外科学会雑誌, 2019)
Congenital factor V deficiency is a congenital bleeding disorder, and its frequency is estimated to be 1 per million population. There has been no report regarding the treatment of oral cancer accompanied by congenital factor V deficiency. In this report, we describe the perioperative management of factor V activity in a tongue cancer patient with congenital factor V deficiency. A 68-year-old woman who had congenital factor V deficiency was referred to our hospital because of an ulcer at the left edge of her tongue. A histopathological examination led to a diagnosis of oral squamous cell carcinoma. Preoperative screening examinations revealed prolonged prothrombin time (PT) and activated partial thromboplastin time (APTT). The factor V activity was 11%. After the preoperative transfusion of 6 units of fresh frozen plasma (FFP), factor V activity was corrected to 30% from 12%, and the patient underwent partial glossectomy functional neck dissection, and tracheotomy under general anesthesia. To perioperatively maintain the factor V activity over 30%, 38 units of FFP were given during 4 days after surgery, and no hemorrhagic complications were observed. At 4 years 2 months after the operation, there has been no sign of recurrence or lymph node metastasis.